Berry Antioxidants in Health and Disease - Dorothy Klimis-Zacas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
During the last decade, a high volume of work has been published on the health-promoting effects of berries (e.g., blueberries, cranberries, blackberries, etc.) that are rich in antioxidant phytochemicals, polyphenols. Consuming a diet rich in polyphenols has been documented to attenuate the risk of chronic diseases, such as cardiovascular disease, certain cancers, diabetes mellitus, and neurodegenerative disorders. Recent evidence also reveals that the biological effects of polyphenols extend beyond their traditional antioxidant role. This Special Issue includes 10 peer-reviewed papers, including original research papers and reviews. They present the most recent advances in the role of berry antioxidants, not only in maintaining health but also in preventing and/or reversing disease both in cell culture, animal models and in humans. Additionally, the molecular mechanisms and signaling pathways modulated by berry antioxidants are presented. Chapters include the role of berry antioxidants in whole fruit and leaves on the metabolic syndrome, obesity, diabetes and glucose intolerance, cancer, inflammation, oxidative stress and neuroprotection as well as cardiovascular disease. As a guest editor, I would like to acknowledge the authors of all chapters for their valuable contributions and reviewers for their thoughtful and constructive suggestions and time. Special thanks to the publishing team of the Antioxidants Journal for their professionalism, attention to detail and timely completion of this volume.